The First Android Based Sharia Fintech Innovation in Indonesia to Increase Inclusive and Literate on Society’s Finance - Suhartono Suhartono; Juniato Sidauruk; Octa Pratama Putra; Syamsul Bahri; Martias Martias; Aan `Rahman; Abdul Hamid; Lukman Hakim; Indria Widyastuti; Badurrachman Abdurrachman; Ninuk Riesmiyantiningtias; Rizky Amalia; Indra Chaidir (Research Synergy Foundation, 2021)
Technology has become the part of today’s people life. Then, it is actually close to the application of it. Absolutely, it has example; such as the electricity for having more sophisticated in financial technology (Fin-Tech). The simplicity and speed of this technology have led people to adopt it in everyday’s life. One of the innovations in developing business and the economy, especially in the banking sector, is currently to develop Fintech (Financial Technology) which is able to facilitate all types of buying and selling transactions, investments and fundraising. Next, the purpose of this study is to explain and provide an understanding of the technical, procedures and benefits of the application, it is called Sharia FinTech. Then, it is also to contribute to the literature on the capacity of the latest technological and non-technological innovations. The research method used is descriptive research method with a qualitative approach. It is to describe and explore the phenomena in the form of engineering human innovation in the financial technology industry. It is done by taking into account the characteristics, quality, and interrelationships between activities It has several aspects; they are: conducting the observation, having an interview session, creating the documentation, and the last one is doing the Literature review. The result of this study is to increase the knowledge, skills and confidence of the community in managing personal finances to be better and to provide access to be having convenient and accountable financial services. Afterwards, this study linits on explaining and providing an understanding of the technical, procedure and benefits of Sharia Fintech for all people in need. Thence, the limitation of the research only discusses the role of Islamic Fintech in increasing the public financial inclusion and literacy. As for the the next researchers, they can be even wider by adding the collaboration of fintech and the banking world. The novelty of this research is the use of the android application as a digital platform in financial inclusion and literacy.